PENGARUH DOSIS DAN WAKTU PEMBERIAN PUPUK ORGANIK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN JAGUNG MANIS (Zea mays Saccharata Strut) - Ari Budiyanto; TEGUH SUPRIYADI; SETIE HARIENI (JURNAL ILMIAH AGRINECA, 2017)
The purpose of this study was to determine the effect of dosage and timing of organic fertilizer and their interaction on the growth and yield of sweet corn (Zea mays saccharata Strut).This research method using factorial archetype Randomized Completely Block Design consisting of 2 treatments: 1) dosage of organic fertilizer, which consists of four levels ie dosages of 0 ton / ha (D0), fertilizer dosage 5 ton / ha (D1), fertilizer 10 ton / ha (D2), and a dosage of fertilizer 15 tons / ha (D3). 2) timing of organic fertilizer consists of three levels, namely planting time (W1), one week before planting (W2), and two weeks before planting (W3). The results showed: 1. The treatment dosage very significant effect on the parameters cob length, weight cobs per plant, weight per plant cob without husks, cobs diameter, fresh weight stover, cobs per plot heavy, heavy cob without husks per plot, and the dry weight of stover, significantly the parameters plant height and number of leaves. 2. Treatment time giving real effect on fresh weight parameter stover, no effect on the parameters cob length, weight cobs per plant, weight per plant cob without husks, cobs diameter, plant height, number of leaves, cobs per plot heavy, heavy cob without husks per plot, and the dry weight of stover. 3. The interaction of dosage and time has non sicnificant effect on the parameters cob length, weight cobs per plant, weight of cobs without husks per plant, diameter cobs, stover fresh weight, plant height, number of leaves, cobs per plot heavy, heavy cob without husks per plot , and the dry weight of stover.